Antimicrobial Activity of Clinically Isolated Bacterial Species Against Staphylococcus aureus - Hardy, Britney L.; Bansal, Garima; Hewlett, Katharine H.; Arora, Arshia; Schaffer, Scott D.; Kamau, Edwin; Bennett, Jason W.; Merrell, D. Scott (Frontiers in Microbiology, 2020)
Bacteria often exist in polymicrobial communities where they compete for limited resources. Intrinsic to this competition is the ability of some species to inhibit or kill their competitors. This phenomenon is pervasive throughout the human body where commensal bacteria block the colonization of incoming microorganisms. In this regard, molecular epidemiological and microbiota-based studies suggest that species-specific interactions play a critical role in the prevention of nasal colonization of the opportunistic pathogen Staphylococcus aureus. Despite this, S. aureus exists as part of the microbiota of 25% of the population, suggesting that the interplay between S. aureus and commensals can be complex. Microbiota studies indicate that several bacterial genera are negatively correlated with S. aureus colonization. While these studies paint a broad overview of bacterial presence, they often fail to identify individual species-specific interactions; a greater insight in this area could aid the development of novel antimicrobials. As a proof of concept study designed to identify individual bacterial species that possess anti-S. aureus activity, we screened a small collection of clinical isolates from the Walter Reed National Military Medical Center for the ability to inhibit multiple S. aureus strains. We found that the majority of the isolates (82%) inhibited at least one S. aureus strain; 23% inhibited all S. aureus strains tested. In total, seven isolates mediated inhibitory activity that was independent of physical contact with S. aureus, and seven isolates mediated bactericidal activity. 16S rRNA based-sequencing revealed that the inhibitory isolates belonged to the Acinetobacter, Agromyces, Corynebacterium, Microbacteria, Mycobacterium, and Staphylococcus genera. Unexpectedly, these included seven distinct Acinetobacter baumannii isolates, all of which showed heterogeneous degrees of anti-S. aureus activity. Defined mechanistic studies on specific isolates revealed that the inhibitory activity was retained in conditioned cell free medium (CCFM) derived from the isolates. Furthermore, CCFM obtained from S. saprophyticus significantly decreased mortality of S. aureus-infected Galleria mellonella caterpillars. While future studies will seek to define the molecular mechanisms of the inhibitory activities, our current findings support the study of polymicrobial interactions as a strategy to understand bacterial competition and to identify novel therapeutics against S. aureus and other pathogens.